Hypertext comprehension of deaf and hard-of-hearing students and students with specific language impairment. (February 2017) - Blom, Helen; Segers, Eliane; Hermans, Daan; Knoors, Harry; Verhoeven, Ludo
Abstract: This paper provides insight into the reading comprehension of hierarchically structured hypertexts within D/HH students and students with SLI. To our knowledge, it is the first study on hypertext comprehension in D/HH students and students with SLI, and it also considers the role of working memory. We compared hypertext versus linear text comprehension in D/HH students and students with SLI versus younger students without language problems who had a similar level of decoding and vocabulary. The results demonstrated no difference in text comprehension between the hierarchically structured hypertext and the linear text. Text comprehension of D/HH students and students with SLI was comparable to that of the students without language problems. In addition, there was a similar positive predictive value of visuospatial and not verbal working memory on hypertext comprehension for all three groups. The findings implicate that educational settings can make use of hierarchically structured hypertexts as well as linear texts and that children can navigate in the digital world from young age on, even if language or working memory problems are present.